Поговір як засіб суспільного контролю в ізраїльських кібуцах - Шенгар, А. (Народна творчість та етнографія, 2008)
The Kibbutz is a voluntary form of communal settlement prominent in Eretz Israel from the pre-state, British Mandatory period through the 1960s and 1970s. Due to limited means of communication with the outside world, and the voluntary nature of life on the kibbutz, forms of legends and rumors about settlement members and behavioral patterns served normative and communicative purposes. This article analyzes three such legendary rumors, and points to their functions in terms of communicating information, evaluating behavioral possibilities and reinforcing desired activities. The article considers evolving functions of the legendary rumors, in light of the changing nature of kibbutz life in the 1980s.